Harnessing Innovation for Business Competitiveness in Achieving Sustainable Development Goals - Senadjki, Abdelhak; Awal, Iddrisu Mohammed; Hui Nee, Au Yong; Ogbeibu, Samuel (International Journal of Economics, Management and Accounting, 2026)
This study examines the impact of technological, social, and environmental innovations on the competitiveness of Malaysian SMEs, focusing on how firm characteristics such as age, size, and type of activity moderate these effects. Data from 480 SMEs were analyzed using Partial Least Squares Structural Equation Modeling. The findings reveal that technological innovation positively impacts competitiveness, particularly when influenced by a firm’s age, size, and activity type. Social innovation also has a direct positive effect on competitiveness, highlighting its importance in addressing social problems to boost business performance. Environmental innovation, however, showed an insignificant effect on competitiveness. The study emphasizes the need for integrating business innovations with supportive infrastructure and fostering a culture of social and environmental innovation to enhance competitiveness. It provides valuable insights for strengthening SMEs and encourages a more holistic approach to innovation for long-term competitive advantage.